Development Strategy for Rumah Kayu Futsal Court (The Indonesian Journal of Business Administration, 2015)
Abstract - Futsal court business has developed quickly in the early 2000s in Indonesia. The booming of futsal court business is also happening in Sukabumi, creating a fierce competition among futsal court arenas. As one of the futsal court arenas in Sukabumi, RKFC has faced decreasing revenue due to the many emerging competitors. In order to get feasible solutions, conceptual framework has been conducted to comprehend the business environments by having both qualitative and quantitative methods. To analyze its external environment, Porterâ€™s five forces analysis has been conducted. Current marketing mix and company performance of RKFC have been analyzed to understand its internal environment. Both environmental analyses are written into SWOT analysis, which later turn into strategies by implementing TOWS matrix. The strategies in TOWS matrix are then selected by conducting achievability-effectiveness analysis. Based on this analysis, it is recommended that RKFC implements five chosen strategies focusing on engaging to futsal community in Sukabumi.Â Keywords: competition, TOWS matrix, achievability-effectiveness analysis, futsal community